Work-related physical factors and low back pain among policemen in Kelantan: a cross-sectional study / Sheikh Muhammad Aiman Alhabshee Muhammad Alif Madrid and Siti Nor Ismalina Isa - Muhammad Alif Madrid, Sheikh Muhammad Aiman Alhabshee; Isa, Siti Nor Ismalina (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
Low back pain (LBP) is a commonly reported musculoskeletal disorder among policemen or active-duty officers. Policemen are exposed to a high risk of developing LBP due to their nature of work and strenuous activities. The aims of this study were to determine the prevalence of LBP and the association between LBP with sociodemographic and work-related physical factors. A crosssectional study was conducted among 101 policemen in one police center in Kelantan, Malaysia. A set of self-administered questionnaires including the sociodemographic form, Nordic Musculoskeletal Questionnaire (NMQ) and International Physical Activity Questionnaire (IPAQ) was used as the research instrument. The prevalence of LBP among policemen was 18.8%. The associations between LBP with sociodemographic and physical activity factors were not statistically significant (p>0.05). However, Cramer's V coefficient showed strong associations between LBP with gender, age, marital status, educational level, ranks, duration of work per week and break time (Cramer's V > 0.15). Although this study found non-significant results between LBP and all study variables, the police workforce should be educated with information regarding LBP and its risk factors in order to encourage preventive measures and minimize LBP prevalence. More studies are also warranted for this population.